BUYING BEHAVIOR OF COLLEGE STUDENTS THROUGH SOCIAL MEDIA ADVERTISEMENTS (International Journal of Food and Nutritional Sciences, 2022)
Everyone's life is greatly impacted by social media, but young people's lives are especially affected. The majority of college students' time is spent on Facebook, Instagram, WhatsApp, and other apps. The social networking apps that are highlighted will have an impact on their important decisions. As a result, the vast majority of businesses use social media for marketing purposes. These applications are being used by them for the distribution and sale of products and services. Social media advertisements nowadays have a wider audience among young people. The purpose of this study was to determine how social media advertisements affected college students' purchasing decisions in the Kanniya Kumari district.